ANALISIS KEPATUHAN, TRANSPARANSI DAN AKUNTABILITAS LAPORAN DANA KAMPANYE PARTAI POLITIK DALAM PENGELOLAAN PENERIMAAN DAN PENGGUNAAN DANA KAMPANYE - Andini, Bayu Nurcahyo; Monteiro, Frenqui; Soebandi, Soebandi (Media Mahardhika, 2018)
Campaign fund is the biggest spending of political party. Due to the huge amount of money during the campaign, by conducting this reseach to know and understand does the legislative candidade and political party are lawfull, transparant and accountable to their spending to the public as principle of good governance in democratic country. This is a qualitative reseach method with triangulation in collecting data, analysing, conduct indepth interview where social situation in the office of Sidoarjo KPU, Habib Basuni, CPA public accountant; and the expeert of of government/ contitutional law. Finding shows that, twoelve (12) political parties are unlawfull to their campaign fund report, yet not transparant and accountable to the public because of: high political cost, unsettle of democratic system, weak of law enforcement, lack of political education, unprofesional of political party internal administration and irelevancy of transparancy and accountability towards politacal succession. Therefore, need to have a cmprehensive and holistic  approach to all parth of democratic stakeholders to play their roles toward good  governance in Sodoarjo.